Sampling frequency affects estimates of annual nitrous oxide fluxes - Barton, L.; Wolf, B.; Rowlings, D.; Scheer, C.; Kiese, R.; Grace, P.; Stefanova, Katia; Butterbach-Bahl, K. (Nature Publishing Group, 2015)
Quantifying nitrous oxide (N2O) fluxes, a potent greenhouse gas, from soils is necessary to improve our knowledge of terrestrial N2O losses. Developing universal sampling frequencies for calculating annual N2O fluxes is difficult, as fluxes are renowned for their high temporal variability. We demonstrate daily sampling was largely required to achieve annual N2O fluxes within 10% of the "best" estimate for 28 annual datasets collected from three continents - Australia, Europe and Asia. Decreasing the regularity of measurements either under- or overestimated annual N2O fluxes, with a maximum overestimation of 935%. Measurement frequency was lowered using a sampling strategy based on environmental factors known to affect temporal variability, but still required sampling more than once a week. Consequently, uncertainty in current global terrestrial N2O budgets associated with the upscaling of field-based datasets can be decreased significantly using adequate sampling frequencies.